“Como uma cura desses vazios” o ensino de artes na perspectiva do letramento étnico-racial: um olhar a partir da atuação de professores(as) de artes na cidade de Belém/PA - Costa, Lívia Weyl (2022)
It is understood that racism starts from the belief in a supposed superiority of a certain human group, defined by their physical and cultural characteristics, over other groups (GOMES, 2003; SILVA, 2020). In Brazil, due to the belief in racial democracy, this practice happens in a veiled way (GOMES, 2003; GONÇALVES, 2000) which makes it necessary to think about actions to expose and discuss racism in society. The city of Belém is no exception, and despite the mandatory teaching of Afro-Brazilian and indigenous cultures, parts of Education for Ethnic-Racial Relations (ERER), being established by law, teachers from different areas still face difficulties to being able to apply the theme in the classroom (COELHO E QUADROS, 2018). Taking into account the experiences of racial literacy, expressed in processes that demand rethinking race as an instrument of social, geographic and economic control that acts both on nonwhite people and on white people (GUINIER, 2004; FERREIRA, 2015). And understanding that the teaching of arts, when mobilizing affective processes (BARBOSA, 1985) and generating emotional and cognitive experiences (FERRAZ AND FUSERI, 1993), also manifests itself as an important agent in the processes for students to reflect on the structures of society and how they are affected by them (PEIXOTO, 2001). We sought to understand how, from an interview with five art teachers from the basic education network, and from the lens of ethnic-racial literacy, the ERER is worked on in the city of Belém. The research is qualitative, with a historical-dialectical materialist focus, using life history as a data collection method and some aspects of Bardin’s content analysis as a data analysis methodology. As a result, it was understood that even without using the nomenclature, teachers propose activities that generate literacy experiences, these happen in dialogue with the local culture and seek to value the self-esteem of non-white students. At the same time, the way to achieve an effective and collective application of the ERER still faces a series of challenges, which reinforces the importance of listening to the experiences, desires and opinions of teachers on the subject.